REDUCAO DA CONCENTRACAO ALVEOLAR MINIMA DO ISOFLURANO E DO SEVOFLURANO PELO SUFENTANIL - Vianna, Pedro Thadeu Galvão [UNESP]; Lapa, J. J B [UNESP]; Ganem, Eliana Marisa [UNESP]; Castiglia, Yara Marcondes Machado [UNESP] (My University, 1998)
Background and Objectives - Inhalational anesthetics have a mild analgesic effect. The reduction of alveolar concentration (MAC) of potent volatile anesthesics by increasing plasma concentrations of opioids is desired in inhalational anesthesia. The purpose of this study was to determine the role of sufentanil in reducing sevoflurane and isoflurane MAC. Methods - Thirty eight adult patients of both genders, physical status ASA I or II, submitted to major abdominal procedures were randomly allocated into two groups. Group I (n = 24) received inahalational anesthesia with sevoflurane and Group II (n = 14) received inhalational anesthesia with isoflurane, both diluted in a mixture of N2O (1 liter) and O2 (0.5 liter). A semi-closed system with CO2 absorber and partial reinhalation was used. Ventilation was mechanically controlled. Sufentanil infusion was administered aiming at obtaining 0.5 ng.ml-1 of plasma concentration. Sufentanil plasma concentration was previously calculated by a computer software. End-tidal concentrations were obtained through a gas analyzer and measured at 15 minutes (M1), 30 minutes (M2), 60 minutes (M3), 90 minutes (M4) and 120 minutes (M5). Systolic and diastolic blood pressure (SBP and DBP) and heart rate (RR) were measured during the same periods with the addition of M0 (pre-anesthetic period). Hourly consumption of the inhalational anesthetic agent (IAC), extubation time (ET = time between admission to the recovery room and extubation) and stay in the post anesthesia recovery room (PA-RR) were also measured. Results - Type and duration of surgeries were similar for both groups. There were no statistically significant differences in MAC, SBP, DBP, RR, IAC, TE and PA-RR between groups. Systolic blood pressure in group I (sevoflurane) showed differences among periods F = 3.82 p < O.05; (M2 = M3)(M4 = M5) and M1 had a intermediate value. MAC in group I showed differences among periods F = 9.0 p < 0.05; M1 < M3. MAC in group II also showed differences among periods F = 13.03 p < O.05; M1 < (M2,M3,M4,M5). Conclusions - Both groups had similar behavior when associated to sufentanil in major abdominal surgeries. Group II showed a higher cardiac and circulatory stability.
Effect of sufentanil on the reduction of isoflurane and sevoflurane MAC
Keywords: Analgesics: sufentanil; Anesthetics: inhalational, isoflurane, sevoflurane; analgesic agent; inhalation anesthetic agent; isoflurane; nitrous oxide plus oxygen; opiate; sevoflurane; sufentanil; abdominal surgery; anesthesia; anesthetic recovery; artificial ventilation; clinical article; clinical trial; computer analysis; controlled clinical trial; controlled study; diastolic blood pressure; drug blood level; extubation; gas analysis; heart rate; human; inhalational drug administration; randomized controlled trial; rebreathing; systolic blood pressure